2003
DOI: 10.1590/s0100-879x2003001200013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrolytic lesion of the dorsal raphe nucleus on water intake and sodium appetite

Abstract: The present study determined the effect of an electrolytic lesion of the dorsal raphe nucleus (DRN) on water intake and sodium appetite. Male Wistar rats weighing 290-320 g with a lesion of the DRN (L-DRN), performed two days before experiments and confirmed by histology at the end of the experiments, presented increased sensitivity to the dehydration induced by fluid deprivation. The cumulative water intake of L-DRN rats reached 23.3 ± 1.9 ml (a 79% increase, N = 9) while sham-lesioned rats (SL-DRN) did not e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Taken together, this evidence supports our view that central control of sodium satiety and excretion is regulated by the serotonergic system that originates from the midbrain, but only one study acknowledged that the suppression of ascending serotonergic pathways through DRN electrolytic lesion evokes an increase in sodium appetite (21). Corroborating these findings, other investigators showed that basal c-Fos expression in serotonergic neurons of the DRN decreased after sodium depletion induced by peritoneal dialysis and increased after spontaneous and induced sodium intake, suggesting that there is a tonic inhibition of sodium appetite by serotonergic cells of this nucleus (11).…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Taken together, this evidence supports our view that central control of sodium satiety and excretion is regulated by the serotonergic system that originates from the midbrain, but only one study acknowledged that the suppression of ascending serotonergic pathways through DRN electrolytic lesion evokes an increase in sodium appetite (21). Corroborating these findings, other investigators showed that basal c-Fos expression in serotonergic neurons of the DRN decreased after sodium depletion induced by peritoneal dialysis and increased after spontaneous and induced sodium intake, suggesting that there is a tonic inhibition of sodium appetite by serotonergic cells of this nucleus (11).…”
Section: Introductionsupporting
confidence: 82%
“…Corroborating these findings, other investigators showed that basal c-Fos expression in serotonergic neurons of the DRN decreased after sodium depletion induced by peritoneal dialysis and increased after spontaneous and induced sodium intake, suggesting that there is a tonic inhibition of sodium appetite by serotonergic cells of this nucleus (11). Although we hypothesized the same, when working with DRN electrolytic lesion it is necessary to limit the lesion to the neuronal cell body located in the ventromedial portion of the DRN and to perform longer observations (21).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Behavior, such as drinking and feeding are constantly monitored by 5-HT-containing neurons in mammals and birds. Studies in our laboratory evidenced the serotonergic neurons influence in the sodium appetite and food and water intake behavior (Badauê-Passos Jr et al, 2003;Olivares et al, 2003;Lima et al, 2004;Cavalcante-Lima et al, 2005a,b;Cedraz-Mercez et al, 2005;Medeiros et al, 2005). In rats, peripheral administration of either 5-HT or its precursor 5-HTP induces water intake via renal renin-angiotensin system (RAS) activation (Rowland et al, 1987), however they display opposed effects when centrally applied.…”
Section: General and Experimental Proceduresmentioning
confidence: 95%